KNOWLEDGE, ATTITUDE AND PREVALENCE OF SNUFF USE: A DESCRIPTIVE CROSS-SECTIONAL STUDY AMONG ADULTS IN THE SAGNERIGU MUNICIPALITY OF THE NORTHERN REGION OF GHANA - Salifu, A.; Muktar, A. M.; Yakubu, S. (UDS International Journal of Development, 2023)
This study sought to assess snuff use among adults in the Sagnerigu Municipality of the Northern Region of Ghana. This study employed an analytical study design. The study used simple random sampling technique to sample 272 respondents in the study setting who were aged above 18 years at the time of the study. The research survey was carried out at Sagnerigu Municipality of the Northern Region of Ghana. Adults between the ages of 18 and 65 years participated in the study. Findings from the study showed that, all the respondents representing 100% said they had ever heard about snuff. From the results, 96% said they had ever used snuff at the time of the study. The findings showed that, there was no statistical association between educational status of respondents and use of snuff (p=0.10). The findings however showed that there was an association between occupational status of respondents and use of snuff by respondents (Ï‡2=12.942; P= 0.02). From the results, 56% of the respondents aged 31-35 years dominated with the males leading in all the age categories of snuff use in the study area. From the results, majority of the respondents (81%) agreed with the statement that people take snuff to enable them perform a task. From the results, majority of the respondents (68%) identified that people take snuff to treat diseases such as cold and headache. The prevalence of snuff use was high among the participants in this study, though ignorance of the potential health dangers of snuff was also high. It is recommended that concerted efforts should be made by healthcare workers to discourage the use of all forms of snuff among people at the study area. Keywords: Snuff, Knowledge, Attitudes, Prevalence